A Systematic Review and Comprehensive Analysis of mcr Gene Prevalence in Bacterial Isolates in Arab Countries - Mouayad Zuheir Bakleh; Muhammad Kohailan; Muhammad Marwan; Abdallah Alhaj Sulaiman (MDPI AG, 2024)
Background: The resurgence of colistin has become critical in combating multidrug-resistant Gram-negative bacteria. However, the emergence of mobilized colistin resistance (mcr) genes presents a crucial global challenge, particularly in the Arab world, which includes regions with unique conditions and ongoing conflicts in some parts. Methods: To address this issue, a systematic review was conducted using multiple databases, including Cochrane, PubMed, Scopus, Web of Science, and Arab World Research Source. Results: A total of 153 studies were included, revealing substantial heterogeneity in the prevalence of mcr genes across 15 Arab countries, with notable findings indicating that Egypt and Lebanon reported the highest number of cases. The analysis indicated that the most prevalent sequence types were ST10, ST101, and ST1011, all of which are Escherichia coli strains linked to significant levels of colistin resistance and multiple antimicrobial resistance profiles. Conclusions: By analyzing the diverse findings from different Arab countries, this review lays a critical foundation for future research and highlights the necessity for enhanced surveillance and targeted interventions to address the looming threat of colistin resistance in the region. Systematic review registration: PROSPERO CRD42024584379.